2020
DOI: 10.1161/hypertensionaha.120.15232
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Blood Pressure and Body Mass Index in the National Academy of Sciences–National Research Council World War II Veteran Twin Registry

Abstract: Blood pressure (BP) and obesity phenotypes may covary due to shared genetic or environmental factors or both. Furthermore, it is possible that the heritability of BP differs according to obesity status—a form of G×E interaction. This hypothesis has never been tested in White twins. The present study included 15 924 White male twin pairs aged between 15 and 33 years from the National Academy of Sciences–National Research Council World War II Veteran Twin Registry. Systolic and diastolic BPs, as well as height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Fourth, the BP instruments were adjusted for BMI. Adjusting for an effect of the exposure does not necessarily create bias [ 72 ], correspondingly genetic estimates for BP have been shown to be similar with and without adjustment for BMI [ 73 ]. Using genetic instruments for BP without adjustment for BMI also made little difference to the estimate for total cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the BP instruments were adjusted for BMI. Adjusting for an effect of the exposure does not necessarily create bias [ 72 ], correspondingly genetic estimates for BP have been shown to be similar with and without adjustment for BMI [ 73 ]. Using genetic instruments for BP without adjustment for BMI also made little difference to the estimate for total cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that common genetic factors may for a large part explain the correlation of blood pressure components with BMI. [11][12][13][14] Blood pressure components were moderately correlated with BMI, largely because of shared genetic factors. However, for the association of BMI with brachial SBP and DBP, aortic SBP, and mean arterial pressure, acquired, modifiable factors were also found to be important.…”
Section: Hypertension: Blood Pressure Blood Pressure Components and V...mentioning
confidence: 99%